Influence of acidic metabolic environment on differentiation of stem cell-derived cardiomyocytes - Jiahao, Mao; Fan, Zhou; Junsheng, Mu (Frontiers in Cardiovascular Medicine, 2024)
Stem cell-based myocardial regeneration is a frontier topic in the treatment of myocardial infarction. Manipulating the metabolic microenvironment of stem cells can influence their differentiation into cardiomyocytes, which have promising clinical applications. pH is an important indicator of the metabolic environment during cardiomyocyte development. And lactate, as one of the main acidic metabolites, is a major regulator of the acidic metabolic environment during early cardiomyocyte development. Here, we summarize the progress of research into the influence of pH value and lactate on cardiomyocyte survival and differentiation, as well as related mechanisms.